Prison healthcare service use and associated factors: a cross sectional study in Northwestern Ethiopia - Yesuf, Yassin Mohammed; Birhan, Amlaku Alemu; Birara, Addisu Gedlu; Adimas, Bewket Dereje; Bezabh, Abebe Bahiru; Agmase, Nega Gedefaw (Frontiers in Psychiatry, 2024)
Studies on inmates' Health Care Service (HCS) utilization are scarce globally, infrequent in Ethiopia while findings about the factors associated with HCS utilization are inconsistent. The present study, therefore, examined inmates' HCS utilization and associated socio-demographic and imprisonment related factors in Northwestern Ethiopia. The study employed institutionbased cross sectional research design and data was collected using questionnaire from 422 inmates in three prisons. The questionnaire collected data about prisoners' demographic characters, imprisonment related information and HCS utilization. Descriptive statistical techniques as well as bi-variate and multiple logistic regressions were used to analyse the data. The study found that 72.5%, 66.1% and 13.3% of the inmates, respectively, used medical services, guidance and counseling services, and psychiatric services. Inmates with primary education, with secondary education, and who know the availability of the services were more likely to use medical services. Inmates with accused status were less likely to use medical services than inmates with convict status. Divorced marital status and knowledge of the service availability were associated with high guidance and counseling service use. An increase in the length of stay in the prison was associated with a decrease in psychiatry service use while knowledge of service availability was associated with higher odds of psychiatry service use. There are high medical care service utilization while low mental health care service utilization among inmates in Northwestern Ethiopia. Results of the study implied that there is a critical need for immediate health care service promotion and education measures. Besides, there are also needs for large scale, longitudinal and potentially cross-cultural studies to better understand additional factors that influence inmates' HCS utilization.